The Extent of Challenges Faced by Teachers in the Online Teaching of English Reading to Primary Grades - Lacerna, Yseah Denise; Revilla, Dr. Nerissa (International Journal of Arts, Sciences and Education, 2022)
Literacy proficiency is a universal goal for all elementary school students. As soon as students enter the primary level, they are taught the alphabet, its distinct sound, and word meaning. This goal is especially difficult for language learners, particularly those who are just learning to write and read. The world has become so text-oriented which made writing and reading to be identified as one of the most important skills. As a result of this change, language instructors are affected and are in need of effective techniques to improve these two particular skills. The purpose of this study is to learn more about the challenges that most teachers find in the online teaching of English reading to primary level students and in what degree do these challenges concern the goal of achieving the second language literacy. This research is believed to be beneficial to the educators, community, and other researchers. This could be a basis for an improvement plan to enhance word literacy with the current educational setup as future researchers could find this study a groundwork for forthcoming studies that are also aiming for the advanced development of online teaching strategies of the foundation of reading and writing.